Pengaruh Skeptisme Profesional, Independensi Dan Kompleksitas Auditor Terhadap Kualitas Audit Pada Inspektorat Provinsi Sulawesi Selatan - Indra Gunawan M (STIEM BONGAYA, 2019)
This study aims to determine and analyze the influence of professional skepticism, independence and competence of auditors on audit quality both partially and simultaneously. This study uses primary data obtained from the distribution of questionnaires. The respondents in this study were all auditors working in the Inspectorate Office of South Sulawesi Province. The results of the study show that partially the professional skepticism variable and auditor competence have a positive and significant effect on audit quality. Meanwhile, the independence variable has a negative and not significant effect on audit quality. For the results of the regression test simultaneously the variables of professional skepticism, independence, and auditor competence have a positive and significant effect on audit quality.